PECULIARITIES OF FORMATION OF PROFESSIONALLY IMPORTANT QUALITIES OF CADETS IN EXTREME SITUATIONS (American Journal of Interdisciplinary Research and Development, 2024)
The article considers pedagogical peculiarities of formation of professionally important qualities of cadets in extreme situations, and also lists factors characteristic for young officers. Necessary abilities for development and improvement of cadet's thinking by specific methods are highlighted, also twenty-eight professionally important qualities in cadet's operational activity are highlighted in tabular form. In addition, the necessary phases are outlined, the fulfilment of which contributes to the formation of competences, thinking and development of cadets in the performance of tasks in daily activities.